The Effect of Time Management on Economics Learning Outcomes for Class X SMA Labschool Unesa During Online Learning - izza milenia ariyati; Waspodo Tjipto Subroto (Buana Pendidikan, 2022)
The online learning system is a new challenge for teachers and students in Indonesia. To get maximum learning outcomes during online learning, students need good time management, so students will value time and take advantage of time so that learning outcomes will be in line with expectations. This study aims to analyze the effect of time management on the learning outcomes of class X economic subjects at SMA Labschool Unesa with a total population of 91 students. The type of research used in this research is quantitative research. The data collection method used in this research is to use a questionnaire and the data analysis used in this research is to use simple linear regression analysis. The results of this study state that (1) Time management partially affects student learning outcomes (2) Time management has a positive and significant relationship with student learning outcomes (3) Time management has a positive and significant effect on the learning outcomes of class X students in economics at SMA Labschool Unesa.